Movements of Tufted Duck ringed in Britain: a preliminary assessment - Ogilvie, M A (Wildfowl, 1987)
A total of 1,674 recoveries of Tufted Duck Aythya fuligula ringed in Britain since 1911 were analysed. Ringing of this species has increased greatly in the last ten years, though mainly in south-east England. The ratio of 133 males to 100 females in the recovered birds closely parallels that found in counts and shooting bags. Ringing has been well spread through the year, including that of breeding birds and their young. Tufted Duck from breeding grounds in Iceland and from northern Scandinavia to northern USSR winter in Britain, and adult males from the latter area also moult in Britain. British breeding birds show a degree of abmigration. Breeding females and their young ringed at Loch Leven, Kinross, migrate south-west to Ireland for the winter, but those ringed further south in Britain are mainly sedentary except in hard weather when there is a southward movement, particularly by young males, to France and Iberia. Further ringing of Tufted Duck should be done in areas away from south-east England, and standards of ageing and sexing should be improved.